Ambient concentration of suspended particulate matter and manganese in urban area of Madurai City - Vathana, Vidya; D, Sarala Thambavani (Journal of Research in Biology, 2012)
Air quality in cities is the result of a complex interaction between natural and anthropogenic environmental conditions. Air pollution in cities is a serious environmental problem-especially in the developing countries. In India, millions of people breathe air with high concentrate of dreaded pollutants. The air is highly polluted in terms of suspended particulate matter in most cities. The pollutants, namely suspended particulate matter and Manganese have been named as criteria by environmental protection agency, USA. Suspended particulate matter monitoring was conducted in the urban environment of Madurai in the state of Tamil Nadu. Three ambient air sampling stations were indentified for the collection of suspended particulate matter each at residential, traffic and industrial area. The particulate matter sampling was conducted using recommended instrument for ambient air sampling (high volume sampler). The concentration of Manganese is found to be maximum at industrial area (0.09μg/m3) followed by traffic (0.06μg/m3) and residential area (0.01μg/m3). The concentration of suspended particulate matter in the industrial area is high followed by traffic and residential area (241.1μg/m3, 222.3 μg/m3 and 189.1μg/m3). The results of the study indicate that the air quality of the sampling stations falls under the polluted category.